2006
DOI: 10.1055/s-2005-865849
|View full text |Cite
|
Sign up to set email alerts
|

Modified Nuss Operation for Pectus Excavatum: Design for Decreasing Cardiopulmonary Complications

Abstract: A small subxiphoid incision makes bar implantation easier and has reduced the incidence of major complications in this early experience with 15 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…In cases with an extreme pectus defect, bilateral thoracoscopy may be also helpful [22]. Another method described to improve the safety and efficacy of mediastinal dissection includes making an additional subxiphoid incision for additional elevation [3,4]. Furthermore, single or multiple submuscular or pericostal bar fixation has reduced, or in some series eliminated, bar dislocation [23,24].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In cases with an extreme pectus defect, bilateral thoracoscopy may be also helpful [22]. Another method described to improve the safety and efficacy of mediastinal dissection includes making an additional subxiphoid incision for additional elevation [3,4]. Furthermore, single or multiple submuscular or pericostal bar fixation has reduced, or in some series eliminated, bar dislocation [23,24].…”
Section: Discussionmentioning
confidence: 95%
“…During this procedure, the blunt retrosternal dissection required to pass the corrective bar across the mediastinum is a potentially hazardous maneuver. Different modifications to the original Nuss procedure have included the use of thoracoscopic guidance to avoid inadvertent blind injury to thoracic structures, as well as techniques for reinforcing bar fixation [2][3][4][5]. However, despite a minimally invasive approach, the Nuss procedure is still associated with significant postoperative pain [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…This modification has helped to overcome the problems of broken wires and did not result in any bar flipping. Huang and coworkers [22] suggested using an AO plate with multiple holes instead of the original pectus bar, and steel wire fixation without the use of lateral stabilizers. Park et al [13] described a five-point fixation with wires around the ribs.…”
Section: Discussionmentioning
confidence: 99%
“…Some precautions to ensure safety during the procedure have been mentioned in the literature [4]. Huang et al [11] reported that a subxiphoid skin incision was made to guide a bar and to decrease cardiopulmonary complications. In their modification, however, the subxiphoid operative scar could spoil cosmetic result.…”
Section: Discussionmentioning
confidence: 99%